Deep brain stimulation and spinal cord stimulation for orthostatic tremor: A systematic review. (November 2022) - Boogers, Alexandra; Billet, Alexine; Vandenberghe, Wim; Nuttin, Bart; Theys, Tom; Mc Laughlin, Myles; De Vloo, Philippe
Abstract: Background: Orthostatic tremor is a rare and debilitating movement disorder. Its first-line treatment is pharmacological. For pharmaco-refractory patients, surgical treatment options such as deep brain stimulation (DBS) and spinal cord stimulation (SCS) have been investigated recently. Objectives: We conducted a systematic review of all published outcome and safety data on DBS and SCS for orthostatic tremor patients. Methods: We searched Pubmed and Embase for studies describing orthostatic tremor patients treated with DBS or SCS. We collected all available outcome and safety data and our primary endpoint was the change in unsupported stance duration 1 year postoperatively (±6 months). Results: We included 15 studies, reporting on 32 orthostatic tremor patients who underwent DBS, 4 patients SCS and 2 both. The ventral intermediate nucleus and the zona incerta were targeted in 25/34 and 9/34 DBS cases, respectively. The median stance time at 1 year follow-up was 240 s compared to 30 s pre-operatively (p < 0.001). Stimulation-induced side effects occurred in the majority of patients, but were often transient. Bilateral stimulation appeared more effective than unilateral and stimulation settings were comparable to thalamic DBS for essential tremor. There were insufficient data available to draw meaningful conclusions on the long-term effects of DBS. Due to insufficient data, no conclusions could be drawn on the effects of SCS on orthostatic tremor. Conclusion: DBS may be effective to increase stance time in orthostatic tremor patients in the first year, but further research is necessary to evaluate the long-term effects and the role of spinal cord stimulation. Highlights: DBS and SCS have been performed to treat patients with orthostatic tremor. Data on outcome is scarce. To get an overview, a systematic review was conducted. In 32 reported cases who underwent DBS, median stance time at 1 year follow-up improved from 30 s to 240 s. There is insufficient data on SCS to draw any conclusions from, on this therapy.